2018
DOI: 10.1590/0102-311x00088017
|View full text |Cite
|
Sign up to set email alerts
|

Preconceito relacionado ao peso na conduta nutricional: um estudo com estudantes de nutrição

Abstract: Obesity is associated with psychosocial problems like stigma, discrimination, and bias. Studies have found that nutritionists and nutrition students display negative attitudes and biases toward obese individuals. This study examined the existence of nutrition students' bias toward obese individuals. The students answered questionnaires by completing on-line forms with demographic data and self-reported weight and height and were assigned to one of four randomly selected hypothetical cases of patients referred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 49 publications
0
9
0
10
Order By: Relevance
“…Em jovens adultos, há estudos que destacam o ingresso na universidade 3,4,6 e a influência do uso da mídia social 3,4,[8][9][10] . Devem-se destacar nesse contexto alguns grupos específicos, como o de estudantes de Nutrição, que vem sendo descrito como aquele que apresenta escores elevados de preconceito, quando questionado sobre adiposidade corporal 36 , e elevada frequência de comportamentos alimentares disfuncionais 17,19,28 .…”
Section: Discussionunclassified
“…Em jovens adultos, há estudos que destacam o ingresso na universidade 3,4,6 e a influência do uso da mídia social 3,4,[8][9][10] . Devem-se destacar nesse contexto alguns grupos específicos, como o de estudantes de Nutrição, que vem sendo descrito como aquele que apresenta escores elevados de preconceito, quando questionado sobre adiposidade corporal 36 , e elevada frequência de comportamentos alimentares disfuncionais 17,19,28 .…”
Section: Discussionunclassified
“…Regarding RD, evidence also shows negative attitudes towards PWO, including studies carried out in Brazil [21,22,30,31]. In a systematic review [28], three of four crosssectional studies examining weight bias among dietitians documented the occurrence of weight bias.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These are alarming numbers, but as evidenced, experiencing weight stigma can be damaging to health. Although it has been shown that dietitians and nutrition students can have negative attitudes towards PWO [21,22], the magnitude of these attitudes compared to laypeople in Brazil is unknown. Understanding this magnitude and the contexts that PWO are exposed to the deleterious effects of weight stigma (i.e., general social environment and clinical settings), can inform targeted interventions at the individual and collective levels.…”
Section: Introductionmentioning
confidence: 99%
“…A obesidade é uma doença multifatorial, definida pela Organização Mundial da Saúde (OMS) como acúmulo anormal ou excessivo de gordura.¹ Considerada um problema de saúde pública, a obesidade está relacionada ao aumento de doenças crônicas não transmissíveis, além de morbidade psicológica por conta de preconceito, estigma, discriminação, estresse, insatisfação corporal. [2][3][4] Entretanto, atualmente, há controvérsias em torno da possibilidade de a obesidade realmente ser considerada uma doença, devido a existência de obesos metabolicamente saudáveis, ou seja, indivíduos obesos que não apresentam nenhuma doença secundária convencionalmente relacionada à obesidade.…”
Section: Introductionunclassified
“…O preconceito, quando presente, pode afetar diretamente o indivíduo e afastá-lo do tratamento. 2 Por isso, os profissionais da saúde são o público alvo desta pesquisa, que objetivou avaliar as atitudes de enfermeiros em relação à obesidade e relacionar com o perfil sociodemográfico e de saúde desses profissionais.…”
Section: Introductionunclassified